The Understanding of dharmanirapekṣa (“secular”) in the Nepali Online Newspaper Nagarik - Buß, Johanna (Journal of religion, media and digital culture, 2018)
The term “secular” has long been interpreted in academia either as opposition towards religion or as a neutral position. As a Western concept deeply entangled with Christianity, its application to non-Christian and non-Western societies is highly contested. In our second case study, we focus on media discourse around Nepali democracy as a secular (dharmanirapekṣa) state. The discourse understands dharmanirapekṣa as neutrality or indifference towards all religions, but the idea of opposition is lacking. Secularism is attacked as a Western concept threatening Nepali culture or welcomed as a tool in the fight for recognition of different groups after centuries of domination under high-caste Hindu rule.